End-of-Life Cancer Care Redesign: Patient and Caregiver Experiences in a Lay Health Worker–Led Intervention. (December 2019) - Patel, Manali I.; Moore, David; Coker, Tumaini R.
Importance: The Engagement of Patients with Advanced Cancer (EPAC), comprised of a lay health worker (LHW) who assists patients with advance care planning, is an effective intervention for improving patient experiences and reducing acute care use and total health-care costs. The objective of this study was to assess patients' and caregivers' experiences with the intervention. Methods: We invited all patients enrolled in EPAC and their caregivers to complete an 8-item survey at the end of the intervention and a random 35% sample to participate in a qualitative interview to assess their experiences. At 15-month follow-up, we invited all caregivers of patients who died during the study to participate in a qualitative interview. We analyzed survey responses using bivariate methods and recorded, transcribed, and analyzed interviews using qualitative content analysis. Results: Sixty-nine patients were alive at completion of the intervention and all 30 identified caregivers completed the survey. All viewed the intervention as a critical part of cancer care and recommended the intervention for other patients. In qualitative interviews, among 30 patients, all reported improved comfort in discussing their end-of-life care preferences. In qualitative interviews with 24 bereaved caregivers, all viewed the intervention as critical in ensuring that their loved ones' wishes were adhered to at the end of life. Conclusions and Relevance: Incorporating an LHW into end-of-life cancer care is an approach supported and viewed as highly effective in improving care by patients and caregivers. The LHW-led EPAC intervention is one solution that can significantly impact patient and caregiver experiences.